2020
DOI: 10.3390/metabo10110469
|View full text |Cite
|
Sign up to set email alerts
|

Altered Levels of Desaturation and ω-6 Fatty Acids in Breast Cancer Patients’ Red Blood Cell Membranes

Abstract: Red blood cell (RBC) membrane can reflect fatty acid (FA) contribution from diet and biosynthesis. In cancer, membrane FAs are involved in tumorigenesis and invasiveness, and are indicated as biomarkers to monitor the disease evolution as well as potential targets for therapies and nutritional strategies. The present study provides RBC membrane FA profiles in recently diagnosed breast cancer patients before starting chemotherapy treatment. Patients and controls were recruited, and their dietary habits were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Thus, FA profiling can provide information on the balance of various molecular components in erythrocyte phospholipids. Importantly, findings from this and other groups have substantiated FA‐based membrane lipid profiling as a robust biomarker of lipid metabolic changes in various samples from cancer patients 29,118,119 . PUFAs are mainly sourced from diet and once inside the cell, they are modified to produce more PUFAs, eventually incorporated into cell membranes regulating membrane function.…”
Section: Exploiting Cancer‐associated Lipid Pool Alterations and Memb...mentioning
confidence: 68%
See 2 more Smart Citations
“…Thus, FA profiling can provide information on the balance of various molecular components in erythrocyte phospholipids. Importantly, findings from this and other groups have substantiated FA‐based membrane lipid profiling as a robust biomarker of lipid metabolic changes in various samples from cancer patients 29,118,119 . PUFAs are mainly sourced from diet and once inside the cell, they are modified to produce more PUFAs, eventually incorporated into cell membranes regulating membrane function.…”
Section: Exploiting Cancer‐associated Lipid Pool Alterations and Memb...mentioning
confidence: 68%
“…In addition, alterations in FA pools also govern the interplay between metabolic, genetic, and dietary changes. Going one step further, the same group revealed that using membranes of mature erythrocytes or red blood cells (RBCs) is the best sampling method to assess FA‐based membrane lipidomic changes 29,119 . Extracting RBC membranes for FA analysis is relatively inexpensive and noninvasive, and RBC membrane composition is representative of all FA families.…”
Section: Exploiting Cancer‐associated Lipid Pool Alterations and Memb...mentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that knowledge on fatty acid-based membrane lipidome analysis will expand the understanding of lipid metabolism and individuate related biomarkers which are applicable as translational molecular medicine tools. Because lipids are an important part of human nutrition, especially in evaluating unsaturated fatty acid intakes, integrated molecular diagnostic profiles of breast cancer patients can be envisaged as easy-to-use screening for the design of tailored dietary regimes, as is emerging in recent clinical observational studies [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this ratio was significantly the lowest in the control group of animals and highest in animals supplemented with micro- and nanogenistein. In two of her publications [ 34 , 35 ], Amézaga presented the results of studies that showed the concentration of saturated fatty acids to be lower in cancer patients than in the healthy control group. Since no cell can exist without membranes, the need to build new membranes is a priority in the process of cell replication.…”
Section: Discussionmentioning
confidence: 99%